The Magical Legalism of Marcel Aymé : Charming Rogues and the Suspension of Physical, Natural, and Positive Law - Miller, Jeffrey (Les Cahiers de droit, 2012)
Some of Marcel Aymé’s most delightful work concerns charming rogues, protagonists who lack the heroism of moral outlaws such as Robin Hood or the golem of Jewish literature but act outside the rule of law in a way that is psychologically if not always morally coherent. On other “law and literature” occasions, Aymé employs what is sometimes called fantasy, but has the sardonic bite of magical realism — what this analysis considers “magical legalism”, where individuals circumvent physical, natural, and positive law in attempts to achieve pure self-expression or egocentric notions of justice.